Maternal overweight and obesity and the risk of caesarean birth in Malawi - Owen Nkoka; Peter Austin Morton Ntenda; Thomas Senghore; Paul Bass (BMC, 2019)
Abstract Background Overweight and obese women are at risk of pregnancy and delivery complications. This study investigates the trend and association between maternal overweight and obesity on caesarean births in Malawi. Methods We utilised cross-sectional population-based Demographic Health Surveys (DHSs) data collected from mothers aged 18-49 years in 2004/05, 2010, and 2015/16 in Malawi. The outcome measure was caesarian birth within 5 years preceding the surveys. The main independent variable was maternal Body Mass Index (BMI) measured as weight in kilograms by height in meters squared (kg/m2) and categorized according to the World Health Organization (WHO) guidelines. Generalized estimating equations (GEE) regression models were constructed to analyze total samples of 6795, 4474 and 4363 in 2004/05, 2010 and 2015/16 respectively. Results There was an observed increase in the trend of caesarean births as well as maternal overweight and obesity from 2004 to 2015. The results of the multivariate analyses showed that maternal overweight (adjusted odds ratio [aOR] = 1.35; 95% Confidence Interval [CI] 1.01-1.83) in 2015/16 and (aOR = 1.36; 95% CI: 1.10-1.65) from 2004 to 2015 were risk factors for caesarean births in Malawi. In addition, being obese (aOR = 2.15; 95% CI: 1.12-4.11) in 2004/05, (aOR = 1.66; 95% CI: 1.08-2.55) in 2010, (aOR = 2.18; 95% CI: 1.48-3.21) in 2015/16, and (aOR = 2.16; 95% CI: 1.65-2.84) from 2004 to 2015) increased the risk of caesarean births. In addition, women who had one parity, and lived in the northern region were significantly more likely to have undergone caesarean birth. Conclusions In order to reduce non-elective cesarean birth in Malawi, specific public health programs should be focus on reducing overweight and obesity among women of reproductive age. More focus attention may be given to women with one parity, particularly in the urban and the northern region of Malawi.